Directions for solving personnel problems in the implementation of management accounting system at the enterprise - Giyosov Ilhom Karimovich (Proceedings of The ICECRS, 2019)
This paper investigates the major points of the research on the directions for solving personnel problems in the implementation of the management accounting system at the enterprise. Pieces of evidence from Uzbekistan were stated in the conclusions of the research.